Mobile situation‐aware framework for developing smart mobile software. Issue 12 (31st July 2014) - Park, Joonseok; Kang, Taejun; Yeom, Keunhyuk
ABSTRACT Advances in mobile technology and significantly increasing utilization of mobile devices such as smartphones and tablets have resulted in a paradigm shift from PC‐centric computing to mobile computing. The results of careful analysis conducted of this mobile landscape indicate that there is a growing demand for smart, user‐centric, situation‐aware mobile software. Invariably, concomitant with this demand is the need for methodologies that can provide support the development of this type of software. In this paper, we propose a semantic framework, called the mobile situation‐aware framework, which supports efficient modeling, construction, processing, management, and inference of mobile situation information. The framework comprises two phases, situation modeling and situation construction, and can serve as a guide and a template in the development of situation‐aware applications for the mobile environment. A case study in which mobile situation‐aware framework is utilized in the development of a semantic media player verifies the efficacy of the proposed framework. Copyright © 2014 John Wiley & Sons, Ltd.